Applying blended learning approach into i-Learn / Mohd Zulhelmi Abu Hassan - Abu Hassan, Mohd Zulhelmi (2007)
Blended learning is a wide term that represents learning solutions that are based on a combination of face-to-face lecturing, self-paced e-learning, and the use of various Internet-based or other technologies to deliver the learning content. This paper describes the blended learning as a combination of face-to-face interaction with e learning. This paper reviews some of the students perception on i-learn and their perspective on blended learning. It also analyzes and identifies the comparison between blended learning and e-learning and the elements of blended learning approach. Synchronous elements such as video conference and chat program are main elements that should have in the blended learning approach. The prototype of blended learning elements has been developed and applied into i-learn system. The elements are video conference and chat program. Furthermore, the evaluation process has been conducted to evaluate the functionality of both prototypes.